Dimethyl sulfide chemistry over the industrial era: comparison of key oxidation mechanisms and long-term observations - U. A. Jongebloed; J. I. Chalif; L. Tashmim; W. C. Porter; K. H. Bates; Q. Chen; E. C. Osterberg; B. G. Koffman; J. Cole-Dai; D. A. Winski; D. G. Ferris; K. J. Kreutz; et al. (Atmospheric Chemistry and Physics)
Dimethyl sulfide (DMS) is primarily emitted by marine phytoplankton and oxidized in the atmosphere to form methanesulfonic acid (MSA) and sulfate aerosols. Ice cores in regions affected by anthropogenic pollution show an industrial-era decline in MSA, which has previously been interpreted as indicating a decline in phytoplankton abundance. However, a simultaneous increase in DMS-derived sulfate (bioSO4) in a Greenland ice core suggests that pollution-driven oxidant changes caused the decline in MSA by influencing the relative production of MSA versus bioSO4. Here we use GEOS-Chem, a global chemical transport model, and a zero-dimensional box model over three time periods (preindustrial era, peak North Atlantic NOx pollution, and 21st century) to investigate the chemical drivers of industrial-era changes in MSA and bioSO4, and we examine whether four DMS oxidation mechanisms reproduce trends and seasonality in observations. We find that box model and GEOS-Chem simulations can only partially reproduce ice core trends in MSA and bioSO4 and that wide variation in model results reflects sensitivity to DMS oxidation mechanism and oxidant concentrations. Our simulations support the hypothesized increase in DMS oxidation by the nitrate radical over the industrial era, which increases bioSO4 production, but competing factors such as oxidation by BrO result in increased MSA production in some simulations, which is inconsistent with observations. To improve understanding of DMS oxidation, future work should investigate aqueous-phase chemistry, which produces 82 %–99 % of MSA and bioSO4 in our simulations, and constrain atmospheric oxidant concentrations, including the nitrate radical, hydroxyl radical, and reactive halogens.